The Peripheral Profile of the Chitinase 3-like-1 in Benign Multiple Sclerosis – A Single Centre's Experience - Barcutean, Laura; Hutanu, Adina; Andone, Sebastian; Maier, Smaranda; Balasa, Rodica (CNS & Neurological Disorders - Drug Targets, 2024)
Background: A limited subgroup of multiple sclerosis (MS) patients present with a longterm disease evolution characterized by a limited disease progression, known as benign MS (BMS). Chitinase 3-like-1 (CHI3L1) levels are sensitive to inflammatory processes and may play a role in the pathogenesis of MS. In this observational, cross-sectional study, we aimed to evaluate the implications of serum CHI3L1 and inflammatory cytokines in BMS patients treated with interferon β-1b for over a decade. Methods: We collected serum samples from 17 BMS patients and 17 healthy controls (HC) to measure serum CHI3L1 levels and a Th17 panel of inflammatory cytokines. Serum levels of CHI3L1 were analysed using the sandwich ELISA method and the Th17 panel was assessed using the multiplex XMap technology on a Flexmap 3D Analyzer. Results: Serum CHI3L1 levels did not differ significantly from HC. We identified a positive correlation between CHI3L1 levels and relapses during treatment. Conclusion: Our findings suggest that there are no differences in serum CHI3L1 levels between BMS patients and HC. However, serum CHI3L1 levels are sensitive to clinical inflammatory activity and may be associated with relapses in BMS patients.
Keywords: inflammation